Physico-chemical, nutritional and sensory aspects of the addition of Citrus fruit by-products in gelation products: a systematic review (Research, Society and Development, 2020)
The objective was to carry out a systematic review of studies that analyzed the chemical and nutritional composition of the pulp and by-products of fruits of the genus Citrus. Also, evaluate the effect of adding these by-products on the physicochemical, nutritional and sensory characteristics of jams and similar products. A survey of studies was conducted on the bases Science Direct, PubMed and Lilacs, published between the years 2003-2018, using 37 articles that met all the inclusion criteria. The values for Soluble Solids, Titratable Acidity and Soluble Solids/Titratable Acidity ratio were evaluated only in the fruit pulp. The pulp showed higher contents of ascorbic acid and moisture when compared to the residues. The by-products had high levels of protein, lipid, carbohydrate, dietary fiber, ash, phenolic compounds and antioxidant capacity. In general, the addition of peel of fruits of the genus Citrus in jellies and similar did not change the pH and Titratable Acidity values. However, it increased the content of Soluble Solids and the antioxidant capacity. The use of by-products as an ingredient also improved the nutritional profile of gelled products, since it increased the concentration of phenolic compounds and ascorbic acid. Despite the nutritional benefits, it is observed that the addition of high levels of Citrus peel in jam reduced sensory acceptability. It is concluded that the use of by-products of fruits of the genus Citrus in jams and similar products is a viable alternative, collaborating for the offer of healthy foods and for the reduction of the disposal of organic waste in the environment.